The Role of School Management in Supporting The Implementation of The Merdeka Curriculum in Indonesian Schools in Johor Bahru, Malaysia - Rudiatwoko, Sigit; Karwanto; Mustaji; Amrozi Khamidi; Mochamad Nursalim (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Sarjanawiyata Tamansiswa, 2024)
The study aims to examine the role of school management in supporting the implementation of the